Structural integrity of corroded girth welds in vintage steel pipelines. (1st October 2016) - Hertelé, Stijn; Cosham, Andrew; Roovers, Paul
Highlights: Vague standards' guidance on weld corrosion assessment leads to unnecessary repairs. Load capacity of component scale girth welds showing metal loss has been tested. Covered weld related influence factors: misalignment, strength mismatch, toughness. Digital image correlation visualizes the structural response of damaged welds. Concrete assessment procedure and validity criteria are developed, based on BS7910. Abstract: Girth welds of old steel pipelines and their surrounding heat affected zones are susceptible to corrosion attack. The resulting reduction in wall thickness may reduce the axial load or internal pressure bearing capacity to an unsafe level. Since standards provide limited guidance on weld corrosion assessment, the authors have executed an extensive experimental program to evaluate the axial load bearing capacity of corroded girth welds. To this end, curved wide plate tests have been executed and were analyzed by means of 3D digital image correlation. This paper discusses key influence factors related to weld geometry and material (strength and toughness). Then, the results are used to develop an assessment approach, based on Annex G of BS 7910:2013 and modified to account for the elastic–plastic stress–strain concentration resulting from weld misalignment.